Spreminjanje urbane rabe tal v Ljubljani - Krevs, Marko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2004)
Efforts to improve the knowledge of urban landuse in Ljubljana, and recent problems and perspectives of monitoring the processes of changing of the selected categories of urban landuse in city, municipality and urban region are presented.
Keywords: urbana geografija; mesta; raba prostora; raba tal; Ljubljana